Experimental study of flooding phenomenon in a power plant reflux air-cooled condenser. (25th March 2015) - Berrichon, J.D.; Louahlia-Gualous, H.; Bandelier, Ph.; Clement, P.; Bariteau, N.
Abstract: This paper presents experimental investigations on flooding phenomenon of counter current adiabatic and condensate flows in a vertical and inclined tube. Three two-phase flows are identified: (i) the start of droplet entrainment at the tube bottom, (ii) the post-flooding, and (iii) the flooding onset. Pressure drop is used as criteria to detect flooding and post-flooding superficial airflow velocity. Superficial airflow velocities for which the identified two-phase flows occur are measured for adiabatic counter current flow. Measurements are correlated taking into account the fluids properties, inclinations and liquid superficial velocity. The proposed correlations give the good predictions for steam condensate flow at low pressure where steam upward flow is in counter current with the downward condensate film. Correlations of frictional factor for flooding and post-flooding phenomena are proposed. Good agreements are obtained between pressure drop predictions and experimental data. Highlights: Experimental studies on flooding for adiabatic and condensate flows are conducted. Critical velocity is measured for droplet entrainment; post-flooding, and flooding. Optimal inclination is found for different downward flow rates and two-phase flows. New correlations are proposed for adiabatic flow and steam reflux condensation. Good agreements are found between the predicted pressure drop and measurements.